Exploring the History of Pre-Travel Health Consultation Regarding Dengue Fever Management Among Foreign Tourist Patients at Primary Clinic in Bali, Indonesia - Ni Komang Ari Wahyuni; Made Ririn Sri Wulandari; Ni Komang Purwaningsih (PT. Dilatra Global Advisory, 2025)
Background – Knowledge of dengue fever management is highly beneficial for travelers, including foreign tourists. Tourists with good knowledge of dengue fever are expected to be able to maintain their health during travel. The implementation of a Pre-Travel Health Consultation program is one of the efforts that can be undertaken to improve traveler’s knowledge and to prepare them for safe and healthy travel. Objectives –This study aimed to exploring the history of pre-travel health consultation regarding the dengue fever management among foreign tourist patients at Primary Clinic. Methods – This study employed a cross-sectional design with a sample size of 69 respondents selected through purposive sampling based on inclusion and exclusion criteria. The research instrument used was a questionnaire. Data were analyzed using the univariate analysis to determine the history of pre-travel health consultation regarding the dengue fever management. Results – The results showed that the majority of patients, 42 (60.9%), had previously participated in pre-travel health consultation, and 46 (66.7%) patients had a good level of knowledge regarding dengue fever management. Conclusion – This study is expected to serve as a reference for educational purposes in developing evidence-based nursing, particularly regarding pre-travel health consultation and the level of knowledge of dengue fever management among foreign tourists.